Preparation and application of epoxy oil-based fire-retardant plasticiser with triazine ring structure (THEIC–SBOE). (May 2015) - Feng, G.-D.; Hu, Y.; Zhou, Y.-H.
Abstract : An epoxy oil-based fire-retardant plasticiser with a triazine ring structure [tris(2-hydroxyethyl) isocyanurate-soybean oil emulsion (THEIC-SBOE)] has been prepared by transesterification and epoxidation using tris(2-hydroxyethyl) isocyanurate and soybean oil methyl ester as the main raw materials. The structure of THEIC-SBOE has been characterised by Fourier transform infrared, 1 H-NMR and 13 C-NMR spectroscopies and elemental analysis, and its thermal stability has been measured by thermogravimetric analysis. Its epoxy value and acid value have been determined as 4·3% and 0·60 mg·KOH g −1, respectively. Examination of the morphology of carbon residue from poly (vinyl chloride) by scanning electron microscopy showed THEIC-SBOE to serve as an intumescent flame retardant. The results showed that, with the same plasticiser contents incorporated into poly (vinyl chloride), THEIC-SBOE imparted similar mechanical properties as epoxidised soybean oil. Furthermore, poly (vinyl chloride) blends incorporating the synthesised plasticiser THEIC-SBOE displayed better fire-retardant properties than those incorporating dioctyl phthalate. The limiting oxygen index of such a poly (vinyl chloride) blend reached 28·4 with 35% (w/w) THEIC-SBOE incorporation.